2021
DOI: 10.1016/j.chiabu.2021.105091
|View full text |Cite
|
Sign up to set email alerts
|

Early trauma and associations with altruistic attitudes and behaviours among young adults

Abstract: Background: Childhood and adolescent traumas are exceptionally prevalent worldwide. Despite their high prevalence and substantial impact, little research has investigated the rates and specific types of early trauma by gender. It is also unknown whether the types of early trauma are differentially associated with heightened or hindered prosocial attitudes and behaviours. Objective: To address this gap, this study aims to explore the rates of different types of early trauma (i.e., abuse: sexual, physical, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…We asked participants to answer questions about experiences in nature (4 items, 1 = strongly disagree to 5 = strongly agree), travel experiences (2 items, 0 = no and 1 = yes), trauma as a child (8 items, 0 = no and 1 = yes). Please note for the trauma index we include a poverty item based on the logic employed by scholars who categorize neglect or the "absence of provision of basic needs such as food or a safe home environment: as existing under the broad category of childhood and adolescent trauma" 43,48 . Moreover, scholars have shown how growing up poor can be traumatic for some and may be associated with social rejection 49 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We asked participants to answer questions about experiences in nature (4 items, 1 = strongly disagree to 5 = strongly agree), travel experiences (2 items, 0 = no and 1 = yes), trauma as a child (8 items, 0 = no and 1 = yes). Please note for the trauma index we include a poverty item based on the logic employed by scholars who categorize neglect or the "absence of provision of basic needs such as food or a safe home environment: as existing under the broad category of childhood and adolescent trauma" 43,48 . Moreover, scholars have shown how growing up poor can be traumatic for some and may be associated with social rejection 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Finally, our results also suggest that many American adults who engage environmentally have overcome adversity. Scholars have documented variables that can support someone after they have experienced trauma, such as social support 33,43 . Our findings indicate a possible need for more trauma-informed resources and social support programs for those who engage.…”
Section: Study Implications and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al found that the main reason for adolescents to comply with social distancing norms is to protect others rather than to protect themselves, which is a manifestation of altruistic behavior [11]. Altruistic behavior is voluntary behavior that benefits others [12]. However, altruism is not always opposed to self-interest.…”
Section: Introductionmentioning
confidence: 99%